Transformasi Pendidikan: Mentradisikan Digitalisasi Pendidikan Islam - Abu A'la, Bassam; Makhshun, Toha (JOIES (Journal of Islamic Education Studies), 2022)
Adaptation to technological developments is the key for humans to maintain life activities, including maintaining educational activities. This research attempts to analyze the digitization of education in the Indonesian context. Three things are the focus of discussion here, namely, what policies have been launched by the government towards tertiary institutions in Indonesia to support digitalization of education (DP), what are the impacts of these policies at the level of implications for Islamic tertiary institutions and what are the challenges of digitizing Islamic education in Indonesia? Indonesia. The research design used in this research is descriptive analysis. Data sources are collected from the internet, especially university websites. State Islamic University (UIN) Syarif Hidayatullah Jakarta, UIN Sunan Kalijaga Yogyakarta, UIN Sunan Ampel Surabaya, UIN Ar-Raniry Banda Aceh. The results of this study are that the learning management system (LMS) is a medium that is widely used by UIN as well as using video conferencing or social media such as WhatasApp as a tool in the learning process. However, to make DP a tradition in higher education, UIN does not yet have supporting technology such as digital libraries and learning videos.